The Process of Interpretation of Indonesian Christians on Jewish Culture Through Religious Tourism - Yahya, Marsha Edwina; Boer, Rino Febrianno (GoAcademica Research & Publishing, 2025)
The existence of religious tourism with a variety of cultural phenomena and social systems is quite interesting to study. The researcher's interest is mainly focused on the process of Indonesian Christians in interpreting Jewish culture through religious tourism. The research methodology used is qualitative which emphasizes inductive thinking that produces descriptive data. There are three concepts that strengthen the theory of hope value to examine how Jewish culture in terms of religious aspects, has a wider and deeper impact on all Christians around the world, including Christians from Indonesia, even though Indonesia does not have diplomatic relations with Israel. It examines the attitudes and behaviors Christians have after seeing firsthand and studying the culture of the Jewish religious community and how religious aspects can shape the mindset and behavior of Christians after studying the culture of the Jewish people.